Effects of Parasitic Fractional Elements to the Dynamics of Memristor. (27th June 2019) - Banchuin, Rawid
Abstract : In this research, we study the effects of the parasitic fractional elements to the dynamic of the memristor where both flux- and charge-controlled memristors have been considered. For doing so, the fractional differential equation-based approach has been used for modeling the memristor and the memristor-based circuits under the effects of the parasitic fractional elements where the resulting equations have been solved both analytically and numerically. From the obtained solutions and simulations, the effects of the parasitic fractional elements to the dynamic of the memristor have been studied. We have found that the parasitic fractional elements cause the charge and flux decay of the memristor similarly to the conventional parasitic elements. Moreover, the impasse points of the phase portraits between flux and charge of the memristor-based circuits can also be broken by the parasitic fractional elements. The effects of the order and the nonlinearity of the parasitic fractional elements have also been studied.